2022
DOI: 10.1016/j.enconman.2021.114918
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the combustion of low carbon fuels (hydrogen, methane and coke oven gas) in a spark ignition engine through CFD modeling

Abstract: The use of low carbon fuels (LCFs) in internal combustion engines is a promising alternative to reduce pollution while achieving high performance through the conversion of the high energy content of the fuels into mechanical energy. However, optimizing the engine design requires deep knowledge of the complex phenomena involved in combustion that depend on the operating conditions and the fuel employed. In this work, computational fluid dynamics (CFD) simulation tools have been used to get insight into the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 65 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…Moreover, a computational fluid dynamics (CFD) simulation showed that intermediate spark advance values of COG reduced the combustion pressure and temperature within the cylinder, decreasing NOx emissions and the wall heat transfer. In this way, COG generated the highest power values compared to CH 4 and H 2 at lean air-to-fuel mixtures …”
Section: Coke Oven Gas Combustion To Energymentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, a computational fluid dynamics (CFD) simulation showed that intermediate spark advance values of COG reduced the combustion pressure and temperature within the cylinder, decreasing NOx emissions and the wall heat transfer. In this way, COG generated the highest power values compared to CH 4 and H 2 at lean air-to-fuel mixtures …”
Section: Coke Oven Gas Combustion To Energymentioning
confidence: 95%
“…In this way, COG generated the highest power values compared to CH 4 and H 2 at lean air-to-fuel mixtures. 180 Garcı ́a et al 181 analyzed the environmental impact of the energy recovery of waste streams in steel production by means of the life cycle analysis tool. Coke oven gas and Linz-Donawitz converter gas were evaluated as supplementary fuels to natural gas in different scenarios that were defined according to the energy contribution of natural gas and off-gases.…”
Section: Coke Oven Gas Combustion To Energymentioning
confidence: 99%
“…Hydrogen has several characteristics that make it a promising fuel, such as the large amount of energy released when combusted, i.e., a high calorific value [6,26] (Table 1).…”
Section: Physical Properties Of Hydrogenmentioning
confidence: 99%
“…Calorific value of different fuels under standard conditions of temperature and pressure. Adapted from Zhao et al [6] and Ortiz-Imedio et al [26].…”
Section: Physical Properties Of Hydrogenmentioning
confidence: 99%
“…In recent years academic studies in internal combustion engines, artificial intelligence estimate [10,11], optimization [12,13] and computer-assisted design and analysis environments [14,15] is also supported. The researchers aim to perform analyzes without entering the laboratory environment with calculations based on this type of mathematical modelling.…”
Section: Introductionmentioning
confidence: 99%